Additional record of Rayllianassa amboinensis (de Man, 1888) from Japan, and description of a new species from Okinawa Island, Ryukyu Islands (Crustacea: Decapoda: Axiidea: Callianassidae) - Komai, Tomoyuki; Fujita, Yoshihisa; Maenosono, Tadafumi (Zootaxa, 2014)
Two species referred to the callianassid ghost shrimp genus Rayllianassa Komai & Tachikawa, 2008 are reported herewith. Additional locality records from Japan are provided for R. amboinensis (de Man, 1888), and the synonymy of Callianassa ngochoae Sakai, 1999 with R. amboinensis is discussed. It is shown that R. amboinensis is associated with sponges or alcyonacean soft corals, representing unusual habitats for callianassids. Rayllianassa rudisulcus n. sp. is described on the basis of a single ovigerous female from shallow soft sediment in Ohura Bay, Okinawa Island, Ryukyu Islands. The new species is distinguished from R. amboinensis by the absence of a dorsal oval on the carapace, the antennal peduncle being longer than the antennular peduncle, and the different shape of the third maxilliped. The status of Rayllianassa is also briefly discussed.